Different stakeholders' perspectives on inclusive education in China: parents of children with ASD, parents of typically developing children, and classroom teachers. Issue 9 (28th July 2020) - Su, Xueyun; Guo, Jiajun; Wang, Xiaohui
ABSTRACT: A main purpose of the present study was to examine and compare attitudes toward inclusive education between parents of children with ASD, parents of typically developing children, and classroom teachers in China. The investigators also sought to explore factors influencing different stakeholders' perspectives. An attitude survey was distributed to 14 institutions in Shanghai and Anhui Province in China, including four kindergartens, two elementary schools, four special schools, and four private training agencies. Seven hundred and twelve responses were received, including 170 from parents of children with ASD, 337 from parents of typically developing children, and 197 from classroom teachers. Both multivariate and univariate analyses were conducted to compare differences in attitudes between groups. The results indicate that parents of children with ASD held the most positive attitudes toward inclusion, whereas classroom teachers held the least positive attitudes toward the inclusion of children with ASD. Further analyses revealed that not only were adults' attitudes influenced by their identities as parents or teachers, but their background may also influence how they perceive inclusive education. The findings of the study provided a comprehensive view on how different parties perceive inclusive education of ASD. It also provided empirical evidence that inclusion generally has a positive impact on people's attitudes toward ASD. Implications and suggestions for future research and practices were further discussed in the paper.